2017
DOI: 10.1080/23766808.2017.1295705
|View full text |Cite
|
Sign up to set email alerts
|

Priority areas for biodiversity conservation in mainland Ecuador

Abstract: Ecuador's territory harbors a unique set of species and ecosystems, many of them endemic to the countries' territory and subject to different sources of threat of anthropogenic origin. Despite national and subnational conservation strategies developed in Ecuador to conserve its biodiversity in the long run, including the National System of Protected Areas (PANE) and the forest conservation incentive program SocioBosque (PSB), further actions are needed to mitigate and reverse the effects of threats for the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
74
0
15

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(91 citation statements)
references
References 71 publications
2
74
0
15
Order By: Relevance
“…Van Der Hoek [37] has shown that governmentally protected areas can help to diminish deforestation. In the first paper of this special collection, Cuesta et al [38] used ecosystem maps and species distribution models to identify priority areas for biodiversity conservation in mainland Ecuador. Their study complements current conservation efforts, and can contribute to guide land-use planning at local and national scales.…”
Section: Overview Of Papers In This Special Collectionmentioning
confidence: 99%
“…Van Der Hoek [37] has shown that governmentally protected areas can help to diminish deforestation. In the first paper of this special collection, Cuesta et al [38] used ecosystem maps and species distribution models to identify priority areas for biodiversity conservation in mainland Ecuador. Their study complements current conservation efforts, and can contribute to guide land-use planning at local and national scales.…”
Section: Overview Of Papers In This Special Collectionmentioning
confidence: 99%
“…Numerous putative species of Panabachia (those documented herein as well as others) have yet to be described, further underscoring the importance of conserving high elevation ecosystems. Although most of the sampled sites are already protected areas [75], many high elevation areas across the Ecuadorian Andes are not part of this network of national parks.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, these ecosystems in the coast and western Andes of Ecuador have already been categorized as high priority areas for conservation and as high exposure risk zones (Cuesta et al, ; Sierra, Campos, & Chamberlin, ). Furthermore, given the high phylogenetic diversity of amphibians and even because most of the sites in this study do not have a formal declaration of forest protection, which could allow these forests to be considered as conservation areas of biodiversity (see also Arteaga et al, ; Cuesta et al, ; Lessmann et al, ).…”
Section: Discussionmentioning
confidence: 99%